LMS: A Framework for Mitigating AI Hallucination Risks in Islamic Education: LMS: Framework Memitigasi Risiko AI Hallucination Pendidikan Islam - Prasidha, Angellita Salsabila (Direktorat Pondok Pesantren Universitas Islam Indonesia, 2026)
The rapid adoption of artificial intelligence in Learning Management Systems (LMS) presents a paradox for Islamic education, as it expands access to knowledge while simultaneously risking AI hallucinations that may distort Islamic values, scriptural evidence, and religious understanding. This study arises from such epistemological concerns and aims to develop a framework that is not only technically robust but also aligned with humanistic values and the ethical foundations of Islamic education. Using a qualitative approach involving critical literature review, observation of AI-supported LMS practices, and expert evaluations from Islamic education scholars and practitioners, the research explores the emergence of bias and hallucination risks in digital learning environments. Findings indicate that effective mitigation requires multilayered verification systems, strengthened digital literacy based on maqāṣid principles, the incorporation of explainable AI for transparency, and the active involvement of educators as guardians of scholarly authority. The study offers a novel contribution by emphasizing the humanization of AI through integrating technological design with Islamic pedagogical ethics, thus reducing error risks while reaffirming human dignity and responsibility in the educational process. [Adopsi kecerdasan buatan secara masif dalam Learning Management Systems (LMS) menghadirkan sebuah paradoks bagi pendidikan Islam, yakni di satu sisi memperluas akses terhadap pengetahuan, namun pada saat yang sama menimbulkan risiko halusinasi AI yang berpotensi mendistorsi nilai-nilai Islam, evidensi skriptural, dan pemahaman keagamaan. Kajian ini berangkat dari kegelisahan epistemologis tersebut dan bertujuan merumuskan sebuah kerangka yang tidak hanya tangguh secara teknis, tetapi juga selaras dengan nilai-nilai humanistik serta landasan etis pendidikan Islam. Dengan menggunakan pendekatan kualitatif melalui telaah literatur kritis, observasi terhadap praktik LMS berbasis AI, serta evaluasi pakar dari para sarjana dan praktisi pendidikan Islam, penelitian ini mengkaji kemunculan bias dan risiko halusinasi dalam ekosistem pembelajaran digital. Temuan penelitian menunjukkan bahwa mitigasi yang efektif memerlukan sistem verifikasi berlapis, penguatan literasi digital yang berlandaskan prinsip-prinsip maqāṣid, penerapan kecerdasan buatan yang dapat dijelaskan (explainable AI) guna memastikan transparansi, serta keterlibatan aktif para pendidik sebagai penjaga otoritas keilmuan. Studi ini memberikan kontribusi baru dengan menekankan urgensi humanisasi AI melalui integrasi desain teknologi dengan etika pedagogis Islam, sehingga mampu meminimalkan risiko kesalahan sekaligus meneguhkan kembali martabat dan tanggung jawab manusia dalam proses pendidikan.]